Rites and Wrongs: Anglican Ceremonies after Legal Weddings, 1837–57 - Probert, Rebecca (Studies in church history, 2023)
The Marriage Act 1836 marked an important change in the rites required for a valid marriage, allowing couples to marry in a register office or registered place of worship. For some, however, these unfamiliar rites did not constitute a marriage at all, and in the early 1850s a particular controversy emerged regarding Anglican clergymen who ‘remarried’ couples who had already been legally married under the 1836 Act. This article examines three cases of such ‘remarriages’ and how two of the clergymen involved subsequently found themselves facing prosecution. It analyses the circumstances in which a rite might become a ‘wrong’ in the eyes of the law and traces the impact of these cases on the development of a new provision governing when an additional religious ceremony could take place and, more unexpectedly, on the form of register office weddings.